2005
DOI: 10.1177/0018726705055037
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ overall perception of HRM effectiveness

Abstract: Although the effects of a company’s overall human resources (HR) practices, or HR bundle, have been extensively examined, the effects of employees’ overall perception of HR effectiveness have rarely been studied. The current research examines whether a company’s commitment HR bundle measured at the company level is associated with an employee’s overall perception measured at the individual level, and whether the overall perception influences his/her perceived procedural justice and organizational commitment. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 37 publications
6
105
0
6
Order By: Relevance
“…In this study, we focused on supervisor-related procedural justice because there is flexibility in the way that individual supervisors may interpret and implement performance evaluations and flexible work arrangements. There is empirical evidence that HR practices influence procedural justice perceptions and that, in turn, perceived procedural justice increases employees' commitment to their organisation (Chang, 2005;Edgar and Geare, 2005;Meyer and Smith, 2000). Given that supervisors play a pivotal role in the day-to-day administration of hospital policy, practices and procedures in Canadian hospitals (Laschinger et al, 2008), we predicted that older nurses' assessment of the presence within their hospital of flexible work options and performance evaluation practices targeting older nurses would be significantly positively related to their perceptions of supervisor-related procedural justice.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…In this study, we focused on supervisor-related procedural justice because there is flexibility in the way that individual supervisors may interpret and implement performance evaluations and flexible work arrangements. There is empirical evidence that HR practices influence procedural justice perceptions and that, in turn, perceived procedural justice increases employees' commitment to their organisation (Chang, 2005;Edgar and Geare, 2005;Meyer and Smith, 2000). Given that supervisors play a pivotal role in the day-to-day administration of hospital policy, practices and procedures in Canadian hospitals (Laschinger et al, 2008), we predicted that older nurses' assessment of the presence within their hospital of flexible work options and performance evaluation practices targeting older nurses would be significantly positively related to their perceptions of supervisor-related procedural justice.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…This understanding can only be achieved if 'objective' measures about the content of the system (reported by managers) are complemented by employees' perceptual measures of the system (quality of implementation) (Cappelli and Sherer 1991). Wright et al (2001) found that the two measures of the system differ, although Chang (2005) and Vandenberg et al (1999) found that the actual or 'objective' system has an effect on employees' overall perception of it, whereas Khilji and Wang (2006) found that differences between the two constructs have an effect on performance. Given the lack up to now of studies in SHRM that attempt to understand how differences between the actual and perceived system have an effect on employee-related mediating variables, the main purpose of the present work is to test the mediation of employee attributes between the system (both actual and perceived) and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Bu durum, çeşitli uygulamaların yarattığı etkiyle gelişen çalışma ortamında oluşabilir. Bağlılık tabanlı insan kaynakları uygulamalarının gerçekleştirilmesiyle çalışanların karar alma sürecine katılımlarının artması, yöneticilerle daha etkili iletişim kurabilme olanağına sahip olmaları ve daha fazla eğitim ve geliştirme fırsatları elde etmeleri mümkündür; bu destekleyici ortam, uygulamaların çalışanlar tarafından olumlu yönde algılanmasını ve yönetimin beklentilerinin daha iyi anlaşılmasını sağlayabilir (Chang, 2005 …”
Section: Bağlılık Tabanlı İnsan Kaynakları Sistemiunclassified